The Extent of Maternal Nutritional Knowledge and Practice During Lactation in Kombolcha Town, South Wollo Zone, Ethiopia: A Mixed Study Design - Tessema DG; Girma E; Mekonnen TC; Mebratu W (Dove Medical Press, 2020)
Demissie Gelaw Tessema,1,* Eshetu Girma,2,* Tefera Chane Mekonnen,3,* Wondwosen Mebratu3,* 1PathFinder of Ethiopia, Debre Birhan, Ethiopia; 2Department of Preventive Medicine, School of Public Health, Addis Ababa University, Addis Ababa, Ethiopia; 3Department of Public Health, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia*These authors contributed equally to this workCorrespondence: Tefera Chane MekonnenWollo University, Dessie, EthiopiaTel +251 911587075Email teferachane@gmail.comObjective: The study aimed to assess nutritional practice and its associated factors among lactating mothers in Kombolcha Town, South Wollo Zone, Amhara Region, Ethiopia, 2017.Design and Setting: A community-based cross-sectional study design supplemented with qualitative research was conducted at Kombolcha Town from October 23 to November 10, 2017. A systematic sampling technique was used to select the study participants from listed households and purposive sampling was used for the qualitative inquiry.Participants: A total of 425 lactating mothers were interviewed using a pre-tested structured questionnaire. The data were analyzed using Statistical Package for Social Sciences version 23. For the qualitative data, thematic content analysis was used. Multiple logistic regression was used to evaluate the association between nutritional practice with independent variables.The Results: Lactating mothers who had good nutritional practice and knowledge were 28.7% (95% CI: 24.9%, 33.5%) and 52.0% (95% CI: 47.1%, 57.6%) respectively. This study revealed that government-employed mothers (AOR=6.0, 95% CI: 1.953, 18.485) and mothers with good nutritional knowledge (AOR=3.12, 95% CI: 1.832, 5.318) had statistically significant associations with nutritional practices of lactating mothers.Conclusions and Recommendations: The nutritional practices and knowledge of lactating mothers were low in the study area. The mother’s occupation and nutritional knowledge were significantly associated with nutritional practice. Hence, the provision of maternal nutritional education regarding a healthy diet, and timely and regular dissemination of nutritional information were recommended.Keywords: nutritional knowledge, practice, lactating mother, Kombolcha Town, Ethiopia